Concentration of FDI and regional disparities - The role of regional policy. - Miroslav Sipikal (European Regional Science Association (ERSA), 2010)
Foreign direct investment could be very important external source for economic growth, especially in the less developed countries. Several studies showed strong concentration of FDI in most developed regions of the hosting countries, which lead to increasing regional disparities within these countries. FDI often cause crowd out effects for domestic firms in lagging regions. The article will examines role of regional policy in FDI attraction in order to achieve more regional benefits from FDI. We will analyze most often measures taken by regional policy and its interaction with other policies. We will show case study of several regions in Central Europe as an example.
Keywords: 330